2013
DOI: 10.1088/0004-637x/778/2/176
|View full text |Cite
|
Sign up to set email alerts
|

A Global Wave-Driven Magnetohydrodynamic Solar Model With a Unified Treatment of Open and Closed Magnetic Field Topologies

Abstract: We describe, analyze and validate the recently developed Alfvén Wave Solar Model (AWSoM), a 3D global model starting from the top of the chromosphere and extending into interplanetary space (up to 1-2 AU). This model solves the extended twotemperature magnetohydrodynamics equations coupled to a wave kinetic equation for low frequency Alfvén waves. In this picture, heating and acceleration of the plasma are due to wave dissipation and wave pressure gradients, respectively. The dissipation process is described b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 67 publications
3
112
0
Order By: Relevance
“…We find that the model by Hansteen & Leer (1995) severely underpredicts the electron density and this causes both in-situ charge states and line intensities to be exceedingly low. The 1D model by Cranmer et al (2007) and the 3D model by Oran et al (2013) provide qualitatively similar results: they are able to reproduce line intensities of ions formed at subcoronal temperatures but underpredict the intensities of coronal lines and the plasma frozen-in charge state distribution. The discrepancies are due to the Delay Effect, namely, the difficulty at ionizing that the accelerating fast wind experiences as it travels from its source region in the chromosphere into the corona and interplanetary space.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…We find that the model by Hansteen & Leer (1995) severely underpredicts the electron density and this causes both in-situ charge states and line intensities to be exceedingly low. The 1D model by Cranmer et al (2007) and the 3D model by Oran et al (2013) provide qualitatively similar results: they are able to reproduce line intensities of ions formed at subcoronal temperatures but underpredict the intensities of coronal lines and the plasma frozen-in charge state distribution. The discrepancies are due to the Delay Effect, namely, the difficulty at ionizing that the accelerating fast wind experiences as it travels from its source region in the chromosphere into the corona and interplanetary space.…”
Section: Discussionmentioning
confidence: 67%
“…In order to provide a more consistent comparison with the Hansteen and Cranmer models, which are developed without any observational inputs for the magnetic field strength and geometry corresponding to the particular observations of the solar spectra we use, we chose to use the results obtained with a dipole magnetic field boundary and the Oran et al (2013) version of the model. Landi et al (2012d) found that for almost all elements, the charge state distribution significantly deviates from equilibrium almost everywhere along the wind trajectory by factors up to 10 for some ions.…”
Section: The Michigan Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Separate pressure equations for electrons and protons allow the inclusion of non-ideal MHD processes such as electron heat conduction, radiative cooling and electron-proton heat exchange. For the sake of brevity we will not repeat the full set of governing equations here and refer the reader to Sokolov et al (2013) and Oran et al (2013). It is worthwhile, however, to briefly discuss the wave dissipation mechanism, since it is the only heating mechanism assumed in the model and it controls the magnitude of the Alfvénic perturbations considered in this work.…”
Section: Awsom Model Descriptionmentioning
confidence: 99%
“…In this work we use the recently developed Alfvén Wave Solar Model (AWSoM) Oran et al 2013), a global model of the solar atmosphere driven by Alfvén wave energy, which is propagated and dissipated in both open and closed magnetic field lines. The model extends from the top of the chromosphere and up to 1-2AU.…”
Section: Introductionmentioning
confidence: 99%